Development of a Virtual Metering System Application for High Water Cut Wells with Electric Submersible Pumps (ESPS) – a Case Study for Quifa Field - Asuaje Miguel (EDP Sciences, 2021)
Well surveillance is a mandatory requirement for reservoir characterization and production optimization that every asset must aim for. To guarantee constant monitoring of a single well, installing conventional multi-phases flow meters systems is necessary. As an alternative way, this paper presents a Virtual Metering System (VMS) developed to estimate flow rates in oil wells with high water cut operating with electric submersible pumps as artificial lift systems. The VMS starts from a mathematical model based on production variables, well data, and pump performance curves to estimate fluids flow rates and water cut using a Newton Raphson Multivariate Method. The VMS was implemented in 11 wells in Quifa Field, Colombia. The VMS is constantly feeding by data from the PI System. The VMS results show a deviation of less than 3% in calculating the fluid flow rate and less than 5% in estimating the water cut.